ADVANCES AND CHALLENGES OF EDUCATIONAL POLICIES IN ANGOLA FOR THE INCLUSION OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN PRESCHOOL EDUCATION: PERCEPTIONS OF PRESCHOOL TEACHERS AND EDUCATORS IN THE BENFICA DISTRICT - Madalena Sebastião Pedro Ngombe, Sinclética; Manuel Correia Filho, João; Roa Aleaga, Taimara (Revista Gênero e Interdisciplinaridade, 2025)
Recently, Inclusive Education for children with Special Educational Needs (SEN) in Angola has been a subject of reflection, particularly at the educational level, as the implementation of educational policies in line with international organizations’ recommendations is considered important. From this perspective, the article aims to analyze the advances and challenges associated with Angolan Educational Policies for children with Special Educational Needs in Preschool Education, based on the perceptions of teachers and early childhood educators from the Benfica district for integral development. Thus, the study relied on a qualitative methodology, configured as a case study based on bibliographic and documentary review, which supported the understanding of the Angolan policy focused on the inclusion of these children. Therefore, the results corroborated that, despite the legislative advancements, many challenges still exist in the implementation of Educational Policies that ensure the right to education for all. In fact, there is a willingness to face this Special Education challenge, which is not always easy, but the incompatibilities between the adopted policies, in relation to the real context of educational practice, need better attention and monitoring.